2019
DOI: 10.1111/pce.13500
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting stomatal sensitivity to temperature and soil drought in mature alpine conifers

Abstract: Conifers growing at high elevations need to optimize their stomatal conductance (g s ) for maximizing photosynthetic yield while minimizing water loss under less favourable thermal conditions. Yet the ability of high-elevation conifers to adjust their g s sensitivity to environmental drivers remains largely unexplored.We used 4 years of sap flow measurements to elucidate intraspecific and interspecific variability of g s in Larix decidua Mill. and Picea abies (L.) Karst along an elevational gradient and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 109 publications
(133 reference statements)
1
27
1
Order By: Relevance
“…The share of total root cohesion and root depth increases especially under the warm and dry climate scenario (mohc 8.5). This is in line with previous findings reporting stands dominated by Norway spruce to be highly vulnerable to future drought and heat (Honkaniemi et al, 2020Netherer et al, 2019Peters et al, 2019. Accelerated by canopy disturbances, this leads to a transformation into mixed stands, which, consist of an increasing number of fir, beech and maple trees and thus, on average, lead to higher root reinforcement down to deeper soil layers caused by the change in root system (flat to heart or even tap).…”
Section: Discussionsupporting
confidence: 91%
“…The share of total root cohesion and root depth increases especially under the warm and dry climate scenario (mohc 8.5). This is in line with previous findings reporting stands dominated by Norway spruce to be highly vulnerable to future drought and heat (Honkaniemi et al, 2020Netherer et al, 2019Peters et al, 2019. Accelerated by canopy disturbances, this leads to a transformation into mixed stands, which, consist of an increasing number of fir, beech and maple trees and thus, on average, lead to higher root reinforcement down to deeper soil layers caused by the change in root system (flat to heart or even tap).…”
Section: Discussionsupporting
confidence: 91%
“…This is alarming in view of the projected increased exposure of temperate climate zones to drought events and associated sensitivity of conifer forests to biotic disturbance (Lindner et al, 2010). Despite high vulnerability to water deficits in terms of cavitation risks, northern populations of Pinus spp., and P. abies seem to lack adequate strategies of xylem and stomatal control in order to protect against hydraulic constraints (Isaac-Renton et al, 2018;Peters et al, 2018). For the first time directly relating tree transpiration deficits to attack by I. typographus, Matthews et al (2018) found clear hints for compromised tree defense.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions were monitored at each sampled elevation including hourly T , relative humidity (Onset, USA, U23‐002 Pro; used to calculate VPD) and soil volumetric water content at 10 cm depth (SWC; Decagon, USA, EC‐5). A detailed description of the environmental data and their processing is provided in Peters et al (, b). Long‐term mean annual total precipitation in the valley exceeds 800 mm while mean annual T approximates 5°C.…”
Section: Methodsmentioning
confidence: 99%
“…The values of J s were calculated using species‐specific calibration curves established with cut‐stem calibration method for the two species according to Steppe et al (). For further details on data processing see Peters et al (, b). We characterized tree water use using the first‐order derivative of hourly sap flux density, i.e.…”
Section: Methodsmentioning
confidence: 99%